Observation of minimal and maximal speed limits for few and many-body states - Zitian Zhu; Lei Gao; Zehang Bao; Liang Xiang; Zixuan Song; Shibo Xu; Ke Wang; Jiachen Chen; Feitong Jin; Xuhao Zhu; Yu Gao; Yaozu Wu; et al. (Nature Communications)
Abstract Tracking the time evolution of a quantum state allows one to verify the thermalization rate or the propagation speed of correlations in generic quantum systems. Inspired by the energy-time uncertainty principle, bounds have been demonstrated on the maximal speed at which a quantum state can change, resulting in immediate and practical tasks. Based on a programmable superconducting quantum processor, we test the dynamics of various emulated quantum mechanical systems encompassing single- and many-body states. We show that one can test the known quantum speed limits and that modifying a single Hamiltonian parameter allows the observation of the crossover of the different bounds on the dynamics. We also unveil the observation of minimal quantum speed limits in addition to more common maximal ones, i.e., the lowest rate of change of a unitarily evolved quantum state. Our results show a comprehensive experimental characterization of quantum speed limits and enhance the understanding for their subsequent study in engineered non-unitary conditions.